A new anamorphic genus from India - and N.K. RAO, C. MANOHARACHARY, D.K. AGARWAL* (Indian Phytopathology, 2004)
A new anamorphic dematiaceous hyphomycete genus Cylindromyces striatus characterized by micronematous conidiophores and monotrectic conidiogenous cells producing cylindrical, longitudinally striate and transversely septate conidia is described.